Analytics and Management Reporting Tools and Digital Transformation in Uzbek Retail - Mikhailovna, Djumaniyazova Sabina (Academia Open, 2025)
General Background: Retail trade plays a critical role in Uzbekistan’s economy, contributing significantly to growth, employment, and consumer satisfaction. Specific Background: While the sector has experienced rapid revenue expansion over the past decade, digital transformation remains unevenly distributed, especially between large enterprises and small businesses. Knowledge Gap: Despite notable progress, small and medium-sized retailers struggle to implement advanced analytics and management reporting due to resource constraints, lack of expertise, and infrastructure limitations. Aims: This study aims to evaluate the current state, challenges, and prospects of analytics and management reporting tools within Uzbekistan’s retail sector amid ongoing digital transformation. Results: Findings reveal exponential growth in retail revenue and partial digital adoption, particularly among large chains deploying BI, CRM, and AI tools. However, smaller businesses remain digitally underserved. Novelty: The research presents a systemic framework integrating state support, education, and cloud-based technology adoption to bridge the digital divide and enhance analytical capacity. Implications: The study underscores the need for government-subsidized digital tools, targeted workforce development, and infrastructure investment to ensure inclusive digital progress and sustained efficiency in retail trade across Uzbekistan. Highlight : Retail trade in Uzbekistan is growing steadily but small businesses lag in adopting digital tools. BI, CRM, and AI systems are transforming large retailers, enhancing decision-making and efficiency. Key barriers include specialist shortages, infrastructure gaps, and limited digital access for SMEs. Keyword : Retail Trade, Business Intelligence, Digital Transformation, CRM Systems, Uzbekistan